Developing Cultural Awareness through the Use of Authentic Materials in the EFL Classroom at the Department of Letters and English, University of Frères Mentouri Constantine 1 - Benhamlaoui, Amina; Belouahem, Riad (Journal of Human Sciences, 2022)
Language and culture are two intricately linked concepts in foreign language pedagogy, and dealing with one of the two without taking into account the other has been proven to be impossible without facing a multiplicity of communicative problems. On this ground, countless study works are dedicated to the issue of developing students’ cultural awareness and investigating the most efficient tools that contribute to the reaching of the desired objectives. Thus, this resulted is a call for casting light on the use of authentic materials in the EFL classrooms. Authentic materials constitute a convenient teaching tool which serves the aims of equipping students with necessary cultural knowledge and skills, boosting students’ motivation and interest towards cultural diversity, and making the teaching/learning process enjoyable and easier. Therefore, the present paper endeavours to investigate students’ view on promoting their cultural awareness through the use of authentic materials in the EFL classroom. In order to collect data about the validity of authentic materials in developing students’ cultural awareness, a questionnaire is used as a research tool. The latter is administered to a sample of 98 master two students extracted from a population of 327 master two students at the department of Letters and English, University of Frères Mentouri Constantine1. The obtained results revealed that authentic materials are worth integration in the EFL classrooms for motivating students and developing their cultural awareness.